Aamra - Mondal, Sahiful (India : Center for Communication and Development, 2005)
Sahiful Mondal is one of more than 500 children rescued from child labour by Swapan Mukherjee, founder of Muktaneer (meaning Open Sky), a home for destitute children in Kolkata. Part of a bigger project at Kolkata children’s home, Sahif directed “Aamra”, a film raising questions about the environment.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films